Edukasi Berbasis Self Management Untuk Meningkatkan Self Care Pada Diabetes Mellitus Tipe 2 - Susy Puspasari; Cecep Imam Hardiansyah; Gina Nurdina; Herdiman Herdiman; Septa Permana; Tri Antika Rizki Kusuma Putri (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Diabetes Mellitus disease is a serious public health problem faced in the world, diabetes is a chronic disease that occurs because the pancreas does not produce enough insulin (hormones that regulate blood sugar or glucose), as a result of which metabolic disorders are characterized by sugar levels that exceed normal limits. Self care diabetes consists of independent actions performed by diabetic clients in daily life with the aim to control blood sugar which includes dietary activities, physical exercise, monitoring blood sugar levels, taking medications and foot care. Diabetes Self Management Education (DSME) is a diabetes education that can be a place for diabetic patients to get education and maintain the behavior of diabetic patients.  Objective: To improve self care in people with diabetes mellitus through diabetes self management education against Method: This public service was conducted by discussion using booklet as media information Result: All the participants were attend 100% for all sessions. The self care result shos improvement after DSME have been delivered. Conclusion: The results of this community service show an increase in self-care behavior in individuals with Type 2 Diabetes Mellitus after giving Diabetes Self Management Education. As for educational activities can be carried out by involving more participants and can also involve the patient's family in the educational process with the hope of increasing family support for patients when carrying out self-care.